Carbon Management for the Agricultures in European Union - Serrão, Amílcar (2016)
This paper uses a nontraditional DEA approach to modeling carbon emissions from the agriculture in each one of European Union countries as an undesirable output. We proposed a zero sum gains DEA model with hybrid returns to scale to reallocate carbon emissions from the agriculture in each one of European Union countries using efficiency measures. Model results suggest that agriculture, which has already exceeded their limits, must reduce pollution or negotiate a quota with others. This reallocation strategy creates a carbon management,, without changing the total sum of carbon emissions from the agriculture in European Union countries.